Role of Programmed Cell Death Protein-1 and Lymphocyte Specific Protein Tyrosine Kinase in the Aryl Hydrocarbon Receptor- Mediated Impairment of the IgM Response in Human CD5+ Innate-Like B Cells - Zhou, Jiajun; Blevins, Lance K.; Crawford, Robert B.; Kaminski, Norbert E. (Frontiers in Immunology, 2022)
Innate-like B cells (ILBs) are a heterogeneous population B cells which participate in innate and adaptive immune responses. This diverse subset of B cells is characterized by the expression of CD5 and has been shown to secrete high levels of immunoglobulin M (IgM) in the absence of infection or vaccination. Further, CD5+ ILBs have been shown to express high basal levels of lymphocyte specific protein tyrosine kinase (LCK) and programmed cell death protein-1 (PD-1), which are particularly sensitive to stimulation by interferon gamma (IFN). Previous studies have demonstrated that activation of the aryl hydrocarbon receptor (AHR), a cytosolic ligand-activated transcription factor, results in suppressed IgM responses and is dependent on LCK. A recent study showed that CD5+ ILBs are particularly sensitive to AHR activation as evidenced by a significant suppression of the IgM response compared to CD5- B cells, which were refractory. Therefore, the objective of this study was to further investigate the role of LCK and PD-1 signaling in AHR-mediated suppression of CD5+ ILBs. In addition, studies were conducted to establish whether IFN alters the levels of LCK and PD-1 in CD5+ ILBs. We found that AHR activation led to a significant upregulation of total LCK and PD-1 proteins in CD5+ ILBs, which correlated with suppression of IgM. Interestingly, treatment with recombinant IFN reduced LCK protein levels and reversed AHR-mediated IgM suppression in CD5+ ILBs in a similar manner as LCK inhibitors. Collectively, these results support a critical role for LCK and PD-1 in AHR-mediated suppression of the IgM response in human CD5+ ILBs.